Towards an integrated model of strategic environmental communication: advancing theories of reactance and planned behavior in a water conservation context. Issue 2 (4th March 2018) - Liang, Yuhua (Jake); Kee, Kerk F.; Henderson, Lauren K.
ABSTRACT: This study demonstrates how communication research can be strategically applied to address environmental problems in modern societies. To accomplish this goal, this research advances an integrated communication model based on psychological reactance theory and the theory of planned behavior to explain negative attitude change that can occur when people are exposed to water conservation campaigns [Liang, Y. J., Henderson, L.K., & Kee, K. F. (2017). Running out of water! Developing a message typology and evaluating message effects on attitude toward water conservation. Environmental Communication . doi:10.1080/17524032.2017.1288648 ]. The data fit the hypothesized model, synthesizing message-, social-, and individual-based processes to predict their effects on behavioral intention towards water conservation. Interestingly, data show that (1) combinations of message strategies affect reactance differently, and (2) subjective norm and perceived behavioral control negatively correlated with threat to freedom. These results point to the practical implication that environmental communication to promote voluntary water conservation are effective when campaign messages are designed to reduce threat to freedom, induce social norms, and increase self-efficacy. We call the documented research process strategic environmental communication, which focuses on the joint application of evidence and theory towards addressing environmentally motivated problems.